A stochastic seaport network retrofit management problem considering shipping routing design. (January 2016) - Peng, Yun; Wang, Wenyuan; Guo, Zijian; Song, Xiangqun; Zhang, Qi
Abstract: Seaports are exposed to various uncertain disasters caused by natural or human factors, which have multi-dimensional impacts on the economy. Retrofit appears as one of the effective mitigation methods to protect the seaport network and to reduce the post-disaster loss in the port management engineering. The post-disaster loss is quantified by replacement or repair cost of the structural damage and travel delay loss of vessels. Therefore, given a set of seaports, this paper aims to provide solutions for which seaports should be retrofitted in order to minimize the damage loss due to unpredictable disasters. We first present a network representation of a seaport shipping network. Based on the network, a two-stage stochastic programming model is formulated with a sub-model of the shipping routing design. Benders decomposition method is then used to solve the mixed-integer non-linear problem. Finally, we apply the two-stage model to solve the retrofit problem of eight mainline seaports in China Mainland. The real-time case study shows that the proposed model is efficient to get good solutions. Highlights: Retrofit appears as one of the effective mitigation methods to reduce the post-disaster loss. This paper aims to provide solutions for which seaports should be retrofitted. A two-stage stochastic programming model is formulated to minimize the damage loss due to unpredictable disasters. Benders decomposition method is used to solve the mixed-integer non-linear problem.